Duration of dialysis increases risk of hepatitis C virus infections among hemodialysis patients in Anambra state, Nigeria - Chizoba, Okeke Okechukwu; Chibuogwu, Ajulu A (Universa Medicina, 2018)
Background Sexually transmitted infections and syphilis are a major public health concern. Hemodialysis patients are at an increased risk of acquiring hepatitis B virus (HBV) and hepatitis C virus (HCV) infection. The aim of this study was to determine the seroprevalence of HBV, HCV, syphilis, and the association between these infections and hemodialysis among hemodialysis patients.MethodsA cross-sectional study was conducted involving 90 hemodialysis patients. Blood samples were collected and analysed for HBV, HCV and syphilis using immunochromatographic test kits. All subjects completed a questionnaire on demographic characteristics and other risk factors. A chi-square test was used to analyse the data.ResultsThe prevalence of HBV, HCV and syphilis infections was 4.4%, 6.7% and 2.2% respectively. Highest prevalence of HBV, HCV and syphilis were found in patients whose duration of dialysis were >1 year, >1 year, and 4 months to 1 year, respectively. Similarly, those who had undergone dialysis for > 10 times had the highest prevalence of these infections. The major risk factor the patients was exposed to was blood transfusion (100%), with those who had been transfused for 5 times having the highest prevalence of HBV and HCV and those transfused twice for syphilis. A significant association was seen between duration of dialysis and HCV infection (p<0.05).ConclusionThis study has demonstrated that duration of dialysis increased HCV infection in hemodialysis patients. The prevalence of HBV, HCV and syphilis in the hemodialysis unit is a warning that universal precautions will be the next challenge for decentralised hemodialysis services.